To compare volumetric dimensions of pharyngeal airway for different dentofacial skeletal patterns - Cone beam computed tomography - Madhura A Jadhav; Veera I Bhosale; Abhijit B Jadhav (Wolters Kluwer Medknow Publications, 2019)
After a century of controversies, we are still not certain on the relationship between airway dimensions and facial morphology. Objective: The objective of the study was to measure nasopharyngeal airway dimensions and compare it among different skeletal patterns. Materials and Methods: Forty-five cone-beam computed tomography (CBCT) scans of patients between 16 and 25 years were used in the study. The nasopharyngeal airway was divided into upper, middle, and lower segments. CBCT images were grouped into skeletal Class I, Class II, and Class III. Results: There is no statistically significant difference between all the three groups for mean height of the upper, middle, and lower pharyngeal airways (P = 0.303, 0.479, and 0.077, respectively). There is no statistically significant difference between all the three groups for mean width of the upper, middle, and lower pharyngeal airways indicated by P = 0.643, 0.791, and 0.99, respectively. There is no statistically significant difference between all the three groups for mean breadth of the upper, middle, and lower pharyngeal airways (P = 0.939, 0.48, and 0.068, respectively). Furthermore, the mean total height of pharyngeal airway in Class I, Class II, and Class III groups indicates no statistically significant difference (P = 0.097). Conclusion: Nasopharyngeal airway dimensions seem to play no role in different skeletal patterns.